PENGEMBANGAN SISTEM INFORMASI CLUB RENANG DENGAN METODE KLASIFIKASI DECISION TREE UNTUK PENENTUAN KELAS PENDAFTARAN BARU : Studi Kasus: Banyu Pratama swimming Club Cilacap - Lusian Nandang Arjamulia; Chrystia Aji Putra; Muhammad Muharrom Al Haromainy (Pusat Riset dan Inovasi Nasional, 2023)
The increase development of information technology has had many impact on various aspects including sports. Management of digitalized sports clubs can make the system more accessible and well documented. The swimming club information system with new registration class classifications is made based on the club requirement. The class determination system was created to facilitate class classification for new members so as not to harm the monthly dues and training portion. The decision tree algorithm is used in making class classification models. Variables for making classifications were obtained based on the number of achievements, 50m freestyle time, mastered style and training distance with three classes namely beginner, semi-achievement and achievement. The classification with C4.5 algorithm, produces an accuracy of 100%. This mean that the C4.5 algorithm can classify new registration classes well.